Frekuensi pemberian pakan untuk pertumbuhan benih ikan Lele Sangkuriang (Clarias gariepinus) - Rakhfid, Abdul; Mauga, Rifai; Fendi, Fendi; Mosriula, Mosriula; Wulan, Wa Ode Sry; Bakri, Muhammad; Alimin, Alimin; Rochmady, Rochmady (Sangia Research Media and Publishing, 2020)
Catfish has various advantages, including fast growth, high adaptability to the environment, delicious taste, and high nutritional content. As a source of nutrition for reared fish, feed is a factor that plays a very important and decisive role in the success of fish farming. The research aims to determine the effect of feeding frequency on the growth and survival of sangkuriang catfish larvae (C. gariepinus). The study was conducted from June to July 2020 at the Abelisawa Fish Seed Center (BBI), Sampara District, Konawe Regency, South East Sulawesi Province using a Completely Randomized Design with three frequencies of feeding treatment, namely treatment A feeding twice a day, treatment B feeding 3 times a day and treatment C feeding 4 times a day with 3 replications. Data were analyzed using Analysis of Variance (ANOVA) at 95% confidence level (a 0,05). The results obtained the highest daily growth in treatment B of 3.11 ± 0.04% per day, followed by treatment A of 2.58 ± 0.05% per day and the lowest in treatment C of 2.53 ± 0.03% per day. The highest absolute growth was obtained in the frequency of feeding 3 times a day at 37.27 ± 0.20 g per individual, followed by 2 times a day at 27.64 ± 0.40 g per individual and the lowest at feeding 4 times a day at 26.51 ± 0.92 g per individual. Survival in all 3 treatments reached 100%. Analysis of variance (α 0.05) shows that different feeding frequencies significantly affect the daily growth rate (0.05>0.00) and absolute growth (0.05>0.00) sangkuriang catfish larvae (C. gariepinus).